The Role Of Ethnomathematics In The Implementation Of Contextual Mathematics Learning - Hadi, Heri Sopian; Supiarmo, M. Gunawan; Tahir, Muhammad; Asroni, Ondi (CV. Global Cendekia Inti, 2024)
This study aiming For know role ethnomathematics in implementation learning mathematics contextual in school basic . As for the method research used​ is studies literature with stages Organize, Synthesize, and Identify . Research results show that ethnomathematics in implementation learning mathematics is one of the solution used For increase interest Study students . In addition ethnomathematics can also present components learning including constructivism , asking , discovering , society​ learning , modeling , reflection and assessment authentic. So that ethnomathematics make it easier student For Study geometry , because context used​ in the form of common culture​ student see , hear and do as member family and society . Learning contextual based on ethnomathematics naturally No only give knowledge about draft geometry only , but also provide knowledge about culture life public Where student is at .